2006
DOI: 10.1111/j.1742-4658.2006.05291.x
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the constitutive active transcription factor CREB by the LKB1‐SIK signaling cascade

Abstract: Cyclic AMP-responsive element (CRE)-binding protein (CREB) is a transcription factor that plays an important role in numerous physiological events, such as cell proliferation, survival, tumorigenesis, glucose metabolism and memory, in a phosphorylation-dependent manner [1,2] Cyclic AMP responsive element (CRE)-binding protein (CREB) is known to activate transcription when its Ser133 is phosphorylated. Two independent investigations have suggested the presence of Ser133-independent activation. One study identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
243
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(259 citation statements)
references
References 38 publications
11
243
1
4
Order By: Relevance
“…As LKB1 has been identified as a key regulator for Crtc2 transcriptional activity (Shaw et al, 2005;Katoh et al, 2006) and because somatic mutations have been identified in a subset of human lung tumors and cell lines (Sanchez-Cespedes et al, 2002;Ji et al, 2007), our data now suggest that enhanced Crtc gene family activity may participate in the tumorigenic process within LKB1 null tumors that are not otherwise associated with the recurrent t(11;19) rearrangement. Interestingly, overexpression of NR4A2 had been previously reported for HeLa and H460 cell lines, which are both known to be LKB1 null (Tiainen et al, 1999;Katoh et al, 2006). NR4A2 has also been tested as a candidate tumor suppressor gene where siRNA knock-down in HeLa cells was associated with parameters of growth inhibition and apoptosis (Ke et al, 2004).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…As LKB1 has been identified as a key regulator for Crtc2 transcriptional activity (Shaw et al, 2005;Katoh et al, 2006) and because somatic mutations have been identified in a subset of human lung tumors and cell lines (Sanchez-Cespedes et al, 2002;Ji et al, 2007), our data now suggest that enhanced Crtc gene family activity may participate in the tumorigenic process within LKB1 null tumors that are not otherwise associated with the recurrent t(11;19) rearrangement. Interestingly, overexpression of NR4A2 had been previously reported for HeLa and H460 cell lines, which are both known to be LKB1 null (Tiainen et al, 1999;Katoh et al, 2006). NR4A2 has also been tested as a candidate tumor suppressor gene where siRNA knock-down in HeLa cells was associated with parameters of growth inhibition and apoptosis (Ke et al, 2004).…”
Section: Discussionsupporting
confidence: 53%
“…We and others had previously shown that Crtc1 is a bona fide cancer gene when activated by a t(11;19) chromosomal translocation resulting in the aberrant transcription of certain Crtc1 inducible genes, including the orphan nuclear receptor NR4A2 (Tonon et al, 2003;Coxon et al, 2005;Wu et al, 2005). As LKB1 has been identified as a key regulator for Crtc2 transcriptional activity (Shaw et al, 2005;Katoh et al, 2006) and because somatic mutations have been identified in a subset of human lung tumors and cell lines (Sanchez-Cespedes et al, 2002;Ji et al, 2007), our data now suggest that enhanced Crtc gene family activity may participate in the tumorigenic process within LKB1 null tumors that are not otherwise associated with the recurrent t(11;19) rearrangement. Interestingly, overexpression of NR4A2 had been previously reported for HeLa and H460 cell lines, which are both known to be LKB1 null (Tiainen et al, 1999;Katoh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LKB1, has been well-documented to be a master upstream activator of AMPK and AMPK-related kinase, activates SIK1, SIK2 and SIK3 by phosphorylation of Thr182, Thr175 and Thr163 residues at their activation loops, respectively (Lizcano et al, 2004). Moreover, the work of Katoh et al (2006) showed the cytoplasmic retention of TORC2 could only be found in the LKB1-deficient HeLa cells when LKB1 was co-transfected with SIK3 into the cell. On the other hand, one point mutation of threonine to glutamate at the 163th residue in SIK3 (T163E) led to constitutive activation of SIK3, which was showed to be sufficient to cause the nuclear export of TORC2 and inactivate cAMP-response element …”
Section: Discussionmentioning
confidence: 99%
“…CRTC1 function thus becomes aberrantly activated, which contributes to CRTC1-MAML2 oncogenic activities (Coxon et al, 2005;Wu et al, 2005). CRTC1 co-activator function is attenuated by salt-induced kinases (SIKs), because SIKs phosphorylate CRTC1, preventing CRTC1 from entering the nucleus and activating CREB transcription (Katoh et al, 2006). As SIKs enzymatic activities are dependent on LKB1, it is anticipated that LKB1 deregulation impacts CRTC1 functional activities.…”
Section: Introductionmentioning
confidence: 99%